2009
DOI: 10.1128/aem.00470-09
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and Interspecies Conjugal Transfer of Tn 916 -Like Elements from Lactococcus lactis In Vitro and In Vivo

Abstract: Tetracycline-resistant Lactococcus lactis strains originally isolated from Polish raw milk were analyzed for the ability to transfer their antibiotic resistance genes in vitro, using filter mating experiments, and in vivo, using germfree rats. Four of six analyzed L. lactis isolates were able to transfer tetracycline resistance determinants in vitro to L. lactis Bu2-60, at frequencies ranging from 10 ؊5 to 10 ؊7 transconjugants per recipient. Three of these four strains could also transfer resistance in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 56 publications
4
33
0
Order By: Relevance
“…The transferability of Tn916 to other bacteria was proven in our laboratory by Boguslawska et al (2009) and was confirmed by others research groups (Agerso et al, 2002;Poyart et al, 2000). Moreover, Boguslawska et al showed that the tet(S) gene can be transferred between bacteria strains, which was likely connected with the presence of the plasmid.…”
Section: Discussionsupporting
confidence: 52%
“…The transferability of Tn916 to other bacteria was proven in our laboratory by Boguslawska et al (2009) and was confirmed by others research groups (Agerso et al, 2002;Poyart et al, 2000). Moreover, Boguslawska et al showed that the tet(S) gene can be transferred between bacteria strains, which was likely connected with the presence of the plasmid.…”
Section: Discussionsupporting
confidence: 52%
“…Numerous studies have already shown that TET resistance is typically transferable and a variety of plasmids have been observed (Boguslawska et al 2009;Kazimierczak et al 2009). There are currently 38 different tet resistance genes described (Cauwerts et al 2006).…”
Section: Tet Tetracycline Ery Erythromycin Mic Minimal Inhibitory Conmentioning
confidence: 96%
“…There are currently 38 different tet resistance genes described (Cauwerts et al 2006). Gene tet(M) encoding ribosomal protection and gene tet(L) determining efflux transporter have been the most often genes identified in poultry enterococci (Boguslawska et al 2009). Acquired resistance to macrolides in enterococci is often associated with the expression of erm(B) (erythromycin-ribosome-methylase) gene (Gupta et al 2009).…”
Section: Tet Tetracycline Ery Erythromycin Mic Minimal Inhibitory Conmentioning
confidence: 99%
“…Transfer of antimicrobial resistance, however, is highly influenced by the complexity of microflora and its interactions with the host. Moreover, it is presumed that in vitro models underestimate the potential risk for resistance transfer compared to in vivo models [58,59]. Therefore, to appropriately assess the risk for horizontal spread of antimicrobial resistance, many authors have recently performed experimental studies under in vivo conditions.…”
Section: Transmission Of Tetracycline and Mls Resistancementioning
confidence: 99%